Wildfire recovery in Pacific Northwest Latine communities: how community capitals shape disaster resilience - Thiel, Amanda M.; Tilt, Jenna; Ellsworth, Lisa; Schmidt, Andres; Hiner, Nancy (Frontiers in Human Dynamics, 2025)
Wildfires are increasingly affecting people’s lives in the Pacific Northwest. Latine populations, in particular, often face unique challenges in their recovery process. This study examines individual Latine wildfire recovery experiences to understand the strengths and barriers in the community’s post-fire recovery process in two wildfire-affected areas in Oregon and Washington. Perceptions of recovery of Latine community members and community-based organizations that serve these populations were collected through focus groups, semi-structured interviews, and participant observation at community events. Results were analyzed using the Community Capitals Framework. Findings reveal that organizational, human, cultural, and social capitals played central roles in shaping recovery. While strong community networks and cultural cohesion facilitated mutual aid, systemic inequities, such as language barriers, exclusion from decision-making, and limited access to formal assistance, hindered recovery. Our findings offer insights into the evolving nature of community disaster recovery and suggest that inclusive disaster response strategies must account for the strengths and structural barriers experienced by vulnerable communities. By centering Latine voices and examining recovery through a community capitals lens, this study contributes a nuanced understanding of how intersecting forms of capital influence recovery. The outcomes provide practical guidance for policymakers, emergency managers, and community organizations seeking to develop more equitable, culturally grounded disaster recovery strategies. This research expands the field’s understanding of community-based recovery by highlighting the importance of relational and cultural strengths, while also identifying points of intervention to reduce vulnerability and promote long-term recovery in underserved populations.